Human Nature from a Comparative Psychological Perspective (American Journal of Islam and Society, 1998)
This paper seeks to advance an understanding of Human Naturethrough Islamic Sources. The paper also seeks to adopt a self-consciouslycomparative approach to psychology, comparing Islamic perspectivewith Western views. The author explores Islamic views on thethree dimensions of psychology - the spiritual, the physiological andthe behavioral. The paper concludes by emphasizing the need for atheoretical basis to define the psychological vision of human nature andto identify the subject matter of psychology within Islamic framework.Psychology cannot be separated from religious, philosophical andmoral issues, the paper insists, therefore it is important that they be integratedin the efforts to articulate Islamic psychology.